2018
DOI: 10.1167/tvst.7.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma-Related Differences in Gaze Behavior When Negotiating Obstacles

Abstract: PurposeSafe navigation requires avoiding objects. Visual field loss may affect how one visually samples the environment, and may thus contribute to bumping into objects and falls. We tested the hypothesis that gaze strategies and the number of collisions differ between people with glaucoma and normally sighted controls when navigating around obstacles, particularly under multitasking situations.MethodsTwenty persons with moderate–severe glaucoma and 20 normally sighted controls walked around a series of irregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 46 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…In the walking track, lower central fixation scores without the remapping condition indicate that the patient gaze was shifted more toward nearby objects, while higher scores with the activated AR DSpecs suggested that patients were looking farther ahead. This observation was in agreement with a previous study that compared normal subjects and glaucoma patients gaze behavior in a walking test [8]. This implies that with AR DSpecs, our patients were demonstrating more normal eye movement behavior.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the walking track, lower central fixation scores without the remapping condition indicate that the patient gaze was shifted more toward nearby objects, while higher scores with the activated AR DSpecs suggested that patients were looking farther ahead. This observation was in agreement with a previous study that compared normal subjects and glaucoma patients gaze behavior in a walking test [8]. This implies that with AR DSpecs, our patients were demonstrating more normal eye movement behavior.…”
Section: Discussionsupporting
confidence: 93%
“…Mobility testing has been reported in PVFL patients [ 8 , 33 , 34 ], to assess the value of new technologies to help patients avoid collisions and assess their perceived FOV. Some implementations with AR headsets minified scene images in front of the eye, including the study by Trese and coworkers [ 9 ], however, no mobility tests were performed as we did with our device.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations